AKURASI METODE CONCORDANCE - DWINING BINTARAWATI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2012)
This research was aimed to examine the accuracy of concordance method on linear method, linear parallel method and equipercentile method. The accuracy of those three concordance methods is revealed through the average score of the root mean square deviation (RMSD). This research used two sets of test instrument, namely the Final Examination of Chemistry, in which each was developed by SMAN 1 Tambun Selatan and SMAN 1 Cikarang Utara. Both of these two sets of test instrument were developed based on similar construct (similar standards of competence and basic competences). The method used was an experimental method. Random Sampling with replacement technique was used. Research hypotheses were tested by using analysis of one way variance (ANAVA). The study concluded that: (1) there was no difference in the average score of the RMSD between the linear methods, parallel linear methods, and equipercentile method when viewed statistically, and (2) viewed empirically, the difference of the average score of the RMSD of the three concordance methods was very small. The average score of RMSD when perceived by the parallel linear method is 3,0964, when perceived by the linear method is 3,1644, and when perceived by the equipercentile methodis 3,2943. This indicated that the parallel linear method was little more accurate compared to both linear method and equipercentile method.